Determination of Inhibitory Action of Allamanda Leaf Extracts Against Some Important Plant Pathogens - Masuduzzaman, S; Meah, MB; Rashid, MM (Journal of Agriculture & Rural Development, 2008)
Allamanda leaf extract and separated compounds were studied to determine their inhibitory efficiency against Phomopsis vexans, Fusarium sp, Rhizoctina solani, Sclerotiurn rolfsii and Phytophthora capsici. Four concentrations of the extract namely 1:1, 1:2, 1:3 and 1:4 were used. Extract at 1:3 concentration completely inhibited mycelial growth of P. vexans while other three concentrations were also near completely inhibitory. No concentration showed good performance to inhibit mycelial growth of Fusarium sp. But all concentrations completely inhibited the growth of mycelia of R. solani. Higher concentration (1:1, 1:2) completely inhibited S. rolfsii whereas lower concentration (1:3, 1:4) arrested its growth to some extent. In case of P. capsici, though 1:3 concentration completely inhibited mycelial growth but other three were also promising. For separated compounds, compound 1 and 3 completely inhibited the growth of P. vexans, the other one was not so much promising. In case of Fusarium sp and R. solani, compound 3 showed partial inhibition, but the same compound completely inhibited the growth of S. rolfsii and P. capsici. Water extract showed better performance compared to separated compounds which indicated that some of the essential compounds for the inhibitory action might have been removed during preparation of extracts in other solvents. Key words: Allamanda, leaf extracts, compounds, plant pathogens, efficiency. doi:10.3329/jard.v6i1.1664 J Agric Rural Dev 6(1&2), 107-112, June 2008